2023
DOI: 10.1084/jem.20221105
|View full text |Cite
|
Sign up to set email alerts
|

Inborn errors of human B cell development, differentiation, and function

Abstract: B cells develop from hematopoietic stem cells in the bone marrow. Once generated, they serve multiple roles in immune regulation and host defense. However, their most important function is producing antibodies (Ab) that efficiently clear invading pathogens. This is achieved by generating memory B cells that rapidly respond to subsequent Ag exposure, and plasma cells (PCs) that continually secrete Ab. These B cell subsets maintain humoral immunity and host protection against recurrent infections for extended pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 202 publications
0
12
0
Order By: Relevance
“…Cellular differentiation is the process by which committed cells undergo drastic gene regulations to become specialized cells. In human, defective differentiation can lead to several disease conditions affecting specific cell lineages such as muscle 42 , B-cells 43 . Here, in pabp2 KD, an increased neoblast population along with a decrease in differentiation corroborates to a defect at lineage progression towards single or multiple cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular differentiation is the process by which committed cells undergo drastic gene regulations to become specialized cells. In human, defective differentiation can lead to several disease conditions affecting specific cell lineages such as muscle 42 , B-cells 43 . Here, in pabp2 KD, an increased neoblast population along with a decrease in differentiation corroborates to a defect at lineage progression towards single or multiple cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic modifications influence several critical signal pathways and therapeutic targeting of this pathway has been showing promising results. Interestingly, PTEN (associated with Multiple Hamartoma Syndrome, OMIM 158350, with overlapping phenotype of tissue overgrowth) was also reported to regulate the PI3K pathway (Tangye et al, 2023 ). It was already demonstrated that over methylation of PTEN promoter inhibits PTEN expression in tamoxifen‐resistant breast carcinoma cells and activates AKT and 5‐Azacytidine (5‐Aza) methylation of the PTEN promoter (Hussain et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…CD19 is normally activated upon hematopoietic stem cell commitment into the B cell lineage, and then progressively increases in expression with onward B cell lineage maturation. It functions as a coreceptor or accessory to the BCR/BTK pathway, signaling into B cell lineage cells via the PI3K/AKT pathway, and in this way contributes to B-lineage differentiation and specialization ( 7 9 ). Given this normal function of CD19, insofar as malignant B cells survive weapon payloads attached to CD19-targeting treatments, the CD19 targeting itself will affect the cellular phenotype, either by the direct inhibition of CD19 function, or indirectly through the selection of cells on the lower end of the CD19 expression spectrum ( Figure 1 ).…”
Section: Darwin and Lamarckmentioning
confidence: 99%